Carbon dioxide and methane gas exchange following sphagnum moss harvesting in boreal peatland - Karjalainen, Satu K.; Anttila, Jani; Maanavilja, Liisa; Hamedianfar, Alireza; Laine, Anna M. (Academic Press, 2025)
Understanding the impacts of Sphagnum moss harvesting on peatland carbon (C) balance is crucial due to its potential rise as an anthropogenic land use. We studied eight nutrient-poor peatlands in Finland, harvested between 2015 and 2021, focusing on net ecosystem exchange of CO2 (NEE) and methane (CH4) emissions. The greenhouse gas fluxes were measured to evaluate the sustainability of harvesting practices. Results showed significant variability in Sphagnum regeneration, with wet strip-harvested sites achieving 2–28% re-establishment in 2–8 years, while drier clear-harvested sites saw minimal spontaneous regeneration in 1–6 years. In addition to vegetation succession, GHG emissions were moisture dependent. In wet sites CH4 emissions increased along with time since harvesting and Eriophorum vaginatum (L.) cover, while dry sites exhibited overall lower CH4 fluxes. Younger (1–2 years post-harvest), dry sites were significant CO2 sources due to low photosynthetic activity. Older dry site with sparse ericoid shrub vegetation acted as CO2 sink. Wet sites initially had lower CO2 sink capacity, but this increased as E. vaginatum spread, and reached a plateau when Sphagnum mosses emerged, highlighting the importance of suitable water table levels for efficient CO2 sequestration.
Keywords: peatlands; vegetation; carbon dioxide; methane; hydrology